Classification of causes and associated conditions for stillbirths and neonatal deaths. Issue 3 (June 2017) - Flenady, Vicki; Wojcieszek, Aleena M.; Ellwood, David; Leisher, Susannah Hopkins; Erwich, Jan Jaap H.M.; Draper, Elizabeth S.; McClure, Elizabeth M.; Reinebrant, Hanna E.; Oats, Jeremy; McCowan, Lesley; Kent, Alison L.; Gardener, Glenn; et al.
Abstract: Accurate and consistent classification of causes and associated conditions for perinatal deaths is essential to inform strategies to reduce the five million which occur globally each year. With the majority of deaths occurring in low- and middle-income countries (LMICs), their needs must be prioritised. The aim of this paper is to review the classification of perinatal death, the contemporary classification systems including the World Health Organization's International Classification of Diseases – Perinatal Mortality (ICD-PM), and next steps. During the period from 2009 to 2014, a total of 81 new or modified classification systems were identified with the majority developed in high-income countries (HICs). Structure, definitions and rules and therefore data on causes vary widely and implementation is suboptimal. Whereas system testing is limited, none appears ideal. Several systems result in a high proportion of unexplained stillbirths, prompting HICs to use more detailed systems that require data unavailable in low-income countries. Some systems appear to perform well across these different settings. ICD-PM addresses some shortcomings of ICD-10 for perinatal deaths, but important limitations remain, especially for stillbirths. A global approach to classification is needed and seems feasible. The new ICD-PM system is an important step forward and improvements will be enhanced by wide-scale use and evaluation. Implementation requires national-level support and dedicated resources. Future research should focus on implementation strategies and evaluation methods, defining placental pathologies, and ways to engage parents in the process.